Sistem Pengukuran Antropometri Digital Menggunakan Sensor Ultrasonik dan Load Cell Berbasis Arduino - Saepul Malik, Ahmad; Seliwati, Seliwati (CV. Green Publisher Indonesia, 2025)
There are still many out there who still use manual height and weight measuring tools that seem complicated, and I have also asked several people about manual height and weight measuring tools, and they said it was a bit complicated, because they had to go first to certain places such as health centers etc. and if you have your own, you have to buy two tools at once, and it cannot be used by one person but must get help from others, so here I want to make a height and weight tool in one tool to make it easier for people to check their height and weight using the Arduino Uno microcontroller prototype method and several other components. Such as Load Cell sensors, HX711, Ultrasonic, I2C 16x2 LCD and Bluetooth modules to check height and weight data on mobile phones or laptops. The existence of this tools is expected to make it easier for people to check their height and weight.